Advancing water justice through a tribally-driven partnership: Designing sustainable rainwater harvesting systems in the Yukon–Kuskokwim delta of Alaska - Pool, Thomas; Williams, Mike; McDonald, Claire; Loderhose, Patrick; Velasco, Jocine; Lefthand-Begay, Clarita (Frontiers in Water, 2023)
Community driven co-design models can help collaborators to respectfully engage in projects that provide much-needed resources and services to underserved communities. For example, partnerships between tribal, academic, and non-profit collaborators have the potential to generate positive outcomes for communities when individual efforts by those same groups may be less successful. However, cultural and spiritual differences between collaborators (particularly tribal and non-tribal) can lead to misunderstandings and negative project outcomes, despite good intentions and an honest effort by collaborators to achieve a common goal. Here, we provide a case study of a community-driven co-design project involving tribal, academic, and private collaborators to design and build a rainwater harvesting system with the Akiak Native Community (ANC), and their tribal council in Alaska, USA. A novel collaborative co-design process honoring the tribal sovereignty of the ANC is emphasized in this case study; a design model that is poorly represented in the literature with real-world examples. Logistics associated with designing and constructing the community-use rainwater harvesting system on Alaskan tribal lands is reviewed but the focus of this work is on the collaborative design process more so than the construction of the water harvesting system end product. More explicitly, the use of multiple approaches to promote collaborator involvement along with an emphasis on developing community driven project goals are highlighted as essential steps in our co-design process.